Artefakty kultury lokalnej w doświadczeniach polsko-niemieckiego pogranicza. Uwarunkowania kształtowania postaw wobec dziedzictwa kulturowego Górnych Łużyc - Dziubacka, Krystyna (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2016)
This article refers to the experiences and conditioning of the cultural legacy of Upper Lusatia, particularly concerning this part, which in consequence of political divisions of 1945, fell to Poland and remained within its borders. The essential part of the reflections entails the analysis of the attitudes of Bogatynia residents (a town in the Polish-German borderland in the south-western Poland, Lower Silesia voivodship) towards the Upper Lusatian (Umgebindehaus) houses, being a part of their cultural landscape. The overall poor technical condition of the latter evokes reflection over the causes of insufficient need of the protection of this area, being a part of the regional cultural heritage. Putting forward the thesis of the leading the role of human factor (i.e. low parameters of the human capital), the significance of historical and economic factors is also emphasized. Seeking ways of saving unique in the European scale Upper Lusatian architecture, the author makes reference to some selected examples of different modes of cooperation undertaken in the course of the recent years between the local communities experiencing similar problems in the Polish-Czech-German tripoint.
Keywords: borderland; cultural legacy; Upper Lusatia; Bogatynia